Efficacy of Multimodal Therapy in the Survival Outcomes of Advanced-Stage (Stage III–Stage IV) Oral Carcinoma Patients: An Institutional Experience in Asian Indian Population - Dhawan, Amit (J Maxillofac Oral Surg, 2017)
AIM: Primary ablative surgery followed by post-op radiotherapy (S-RT) remains the mainstay of treatment for stage III–stage IV oral carcinoma. A retrospective analysis of survival rates of advanced-stage OSCC patients treated with multimodal therapies (S-RT or combined chemoradiation) was performed to analyse the outcome for patient survival and whether addition of adjuvant chemotherapy (S-CRT) improves survival. MATERIALS AND METHODS: Demographic, pathological, treatment and follow-up data of 128 patients were included in the study. Sixty-nine patients received S-RT, while 55 patients were opted for S-CRT. Overall survival, disease-specific survival and disease-free survival were estimated with Kaplan–Meier analysis and compared between groups with Cox regression analysis. RESULTS: Survival was significantly influenced by the type of modality and regional spread of disease. S-CRT group had improved overall, disease-specific, disease-free and metastasis-free survival compared to S-RT group. A survival advantage of 10% was achieved in S-CRT group compared to S-RT group even in patients with extracapsular spread and perineural invasion. CONCLUSION: Addition of adjuvant chemotherapy to S-RT improves survival outcomes in advanced OSCC, especially in patients with regional spread of disease.